Grounded Theory in Practice: Novice Researchers' Choice Between Straussian and Glaserian. (April 2019) - M. Alammar, Fahad; Intezari, Ali; Cardow, Andrew; J. Pauleen, David
Novice researchers face challenges in applying grounded theory and choosing between its two historical approaches—Glaserian and Straussian. Although much has been discussed regarding the differences between the Glaserian and Straussian approaches, these differences can confuse early researchers, leading to the flawed use of grounded theory in management and organizational research. Using three case studies (a PhD graduate, a PhD candidate, and a PhD supervisor) in a management and organizational research context, this article illustrates these key differences and provides guidance for researchers in choosing between them. By providing examples and commentary, this article aims to help researchers to choose and apply the most appropriate form of grounded theory within the field of management and organizational research.